Preservation of healthy and harmonious residential and work environment during urban development - Mitkus, Sigitas; Šostak, Olga Regina (International Journal of Strategic Property Management, 2009)
The article discusses densification of fully urbanised territories, which causes deterioration of living conditions for tenants of neighbouring houses (third parties) due to the negative impact of construction on local environment. Specifically, detection of fundamental right violations during territorial planning is in focus, because not only third parties but also future tenants of the house being constructed suffer loss of healthy and harmonious work and recreational environment as a direct result of such violations. A classifier of fundamental right violations during territorial planning was developed for that purpose. The judicial practice was analysed; persons authorised to contest environmental violations under the Law on Administrative Proceedings and the scope of their authorisation were determined. First Publish Online: 18 Oct 2010